Poverty mapping case studies - Hyman, Glenn G.; Larrea, Carlos; Farrow, Andrew (Consultative Group on International Agricultural Research, 2020)
This project developed data, information and knowledge on the spatial distribution of poverty in eight developing countries. The eight case studies included poverty and food security maps, the data sets, preprints of journal articles for a special issue of Food Policy, standardized geospatial metadata and a browse graphic showing key maps. The different case studies use cutting-edge poverty mapping techniques such as small area estimation. The countries included in the project were Bangladesh, Ecuador, Kenya, Malawi, Mexico, Nigeria, Sri Lanka and Vietnam. The data set also includes data for Honduras. The case studies were published here: https://www.sciencedirect.com/journal/food-policy/vol/30/issue/5